Selection of Potent Inhibitors of Soluble Epoxide Hydrolase for Usage in Veterinary Medicine - Shihadih, Diyala S.; Harris, Todd R.; Kodani, Sean D.; Hwang, Sung-Hee; Lee, Kin Sing Stephen; Mavangira, Vengai; Hamamoto, Briana; Guedes, Alonso; Hammock, Bruce D.; Morisseau, Christophe (Frontiers in Veterinary Science, 2020)
The veterinary pharmacopeia available to treat pain and inflammation is limited in number, target of action and efficacy. Inhibitors of soluble epoxide hydrolase (sEH) are a new class of anti-inflammatory, pro-resolving and analgesic drugs being tested in humans that have demonstrated efficacy in laboratory animals. They block the hydrolysis, and, thus, increase endogenous concentrations of analgesic and anti-inflammatory signaling molecules called epoxy-fatty acids. Here, we screened a library of 2,300 inhibitors of the sEH human against partially purified feline, canine and equine hepatic sEH to identify inhibitors that are broadly potent among species. Six very potent sEH inhibitors (IC50 < 1nM for each enzyme tested) were identified. Their microsomal stability was then measured in hepatic extracts from cat, dog and horse, as well as their solubility in solvents suitable for the formulation of drugs. The trans-4-{4-[3-(4-trifluoromethoxy-phenyl)-ureido]-cyclohexyloxy}-benzoic acid (t-TUCB, 1728) appears to be the best compromise between stability and potency across species. Thus, it was selected for further testing in veterinary clinical trials of pain and inflammation in animals.